Islão Ambivalente: A construção identitária dos muçulmanos sob o poder colonial português - Mário Artur Machaqueiro (Cadernos de Estudos Africanos)
This article wishes to contribute to the study of the historical processes that have been spotting Muslim populations as favourite targets for political analysis and governance. Based on Portuguese and French archives, the article tries to uncover the most conspicuous identity representations that ideologues and members of Portuguese colonial staff built around the Islamic communities of Guinea-Bissau and Mozambique. It shows how those images were related to strategies designed for ruling Muslim populations within the colonialist frame, especially after the outbreak of colonial wars. The main argument of this text is that the semi-peripheral position of Portugal in the world-system gave its identity representations and strategies, namely those regarding colonized Muslims, a character that was deeply ambivalent.